Early Ottoman Reactions Towards French Invasion of Egypt in 1798 - Mohammed, Ibtesam; Tawfeeq, Hoger; Murad, Khalil (Humanities Journal of University of Zakho, 2020)
The French invasion and occupation of Egypt in 1798 led to a chain of reactions by the Ottoman and some European states , especially Britain and Russia. The Ottoman state was concerned directly with that event because Egypt was an important Ottoman province. This paper aims to shed light on early Ottoman reactions towards French occupation of Egypt during July – August 1798 before declaring war against France in 2 September 1798. The paper divided into an introduction about French occupation of Egypt and two topics. The first topic dealt with Ottoman continuous follow-up of the French campaign preparations and the related news. The second topic sheds light on Ottoman early reactions towards French occupation of Egypt before moving to military work with Britain to get the French out of Egypt. The main sources of this paper are unpublished Ottoman documents and other historical sources and references.